2021
DOI: 10.1016/j.amepre.2020.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Hesitancy and Concerns About Vaccine Safety and Effectiveness in Shanghai, China

Abstract: Introduction: Rapidly urbanizing communities in middle-income countries could be sources of vaccine hesitancy, and could create hot spots of low vaccination coverage. This study characterizes vaccine hesitancy in Shanghai and identifies disparities in vaccine safety and efficacy concerns by residency status-a marker for recent migration into the city. Methods: Parents of children aged ≤18 years from immunization clinics in Shanghai were enrolled in summer 2019, with the data analyzed during winter 2019−2020. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 45 publications
3
46
0
Order By: Relevance
“…Other safety-related concerns include the potential side effects and allergic reactions that might happen to those who will be vaccinated. The findings reinforce the results of many international studies that ensuring safety from COVID-19, vaccine safety, effectiveness, and side effects are primary concerns among the public [46,47]. Therefore, any effective measures to promote COVID-19 vaccination should focus on promoting the benefits of vaccination, as well as the safety and effectiveness of the vaccines [4].…”
Section: Discussionsupporting
confidence: 82%
“…Other safety-related concerns include the potential side effects and allergic reactions that might happen to those who will be vaccinated. The findings reinforce the results of many international studies that ensuring safety from COVID-19, vaccine safety, effectiveness, and side effects are primary concerns among the public [46,47]. Therefore, any effective measures to promote COVID-19 vaccination should focus on promoting the benefits of vaccination, as well as the safety and effectiveness of the vaccines [4].…”
Section: Discussionsupporting
confidence: 82%
“…Safety and effectiveness are the two most important indicators for evaluating a new vaccine, and new vaccines undergo substantial tests of their safety and effectiveness before and after coming onto the market [ 10 , 11 ]. Previous studies showed that most parents express concerns about side-effects, safety, and effectiveness [ 12 ]. These concerns may be even more prominent for the COVID-19 vaccine, based on the perceived speed of vaccine development.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, remote parishes were often more difficult to access for vaccinators and possibly less well managed than more urban parishes, a characteristic also found in contemporary societies (52). Secondly, people living in remote rural parishes might be less motivated, more hesitant or even completely opposed to vaccination (53,54). Although we observed a decline in the spatio-temporal variation in vaccination coverage, indicating improvements in the management of the vaccination campaign, the reasons behind this decline remain to be identified.…”
Section: Discussionmentioning
confidence: 99%